The Effect of Ananas comucus Extracted Bromelain Enzyme Addition Under Different pH on the Physicochemical Properties of Cottage Cheese - Sylvia Komansilan; Djalal Rosyidi; Lilik Eka Radiati; Purwadi Purwadi (Faculty of Animal Science Universitas Brawijaya, 2020)
The research aims to analyse the effect of bromelain enzyme addition from Ananas comucus under different pH condition to the physicochemical properties of cottage cheese. The observed variables include protein, fat, moisture, ash and cheese yield. The research was conducted in a completely randomized design with 4 treatments (K1 = pH 4.5; K2 = pH 4.6; K3 = pH 5.4; and K4 = pH 5.5) and 4 replications. All of the data were analysed with analysis of variance (ANOVA) and followed with least significant difference (LSD) test. The results showed that the bromelain addition under pH 4.6 showed the best physicochemical properties of cottage cheese that had lowest fat content (0.67 Â± 0.53 %) and highest yield (18.15 Â± 0.22 %) compared to other pH condition, while the protein and ash content did not show any significant difference on all pH condition.